HARMONIZATION OF BENEFITS AND JUSTICE IN LEGAL PROTECTION FOR CONSUMERS - Fransiska Novita Eleanora; Mutiah Nur Syifa; Chika Dwi Imelia; Priska Laurensia (Progressive Law Review, 2023)
Consumers are everyone who uses goods and/or services available in society, both for their own interests, as well as for their families and other people as well as other living things and not for trading. In practice, of course, business actors are responsible for the goods and services consumed by consumers, and if the goods and services are in accordance with what was agreed upon, it will provide benefits for consumers, but if it turns out that the goods or services purchased do not provide the results desired by consumers, such as experiencing damage, hidden defects, the consumer has the right to ask for compensation from business actors, and it is given in accordance with consumer rights based on the principle of justice so that legal protection for consumers can be fulfilled. The purpose of this study is to find out how the principles of benefit and justice are harmonized in providing legal protection for consumers, including in fulfilling the existence of fair compensation in resolving consumer disputes with business actors, so that harmony with the principles of benefit and justice can provide legal protection for consumers and responsibilities to business actors in accordance with their respective rights and obligations